Textile fine grined mortar containing palm oil fuel ash as a partial cement replacement for flexural strengthening on reinforced concrete beams - Wan Yusof, Wan Yuslinda (2018)
Reinforced concrete (RC) beams represents a large percentage of the structure in buildings. As the beams structures known as bending elements, thus most of the structures are often exposed to bending loads, which can affect in serious deteriorations such as concrete cracking and spalling. Due to these factor, Textile Fine Grained Mortar with Palm Oil Fuel Ash (TFGM-POFA) as an upgrading strengthening method of concrete structure. Fine Grained Mortar inclusion POFA (FGM-POFA) with size 40 mm x 40 mm x 160 mm consist of fine sand less than 1 mm, ordinary Portland cement (OPC) and POFA as a partial OPC replacement. Flexural and compressive test was conducted to identify the optimum FGM-POFA. After that, the strengthening on concrete prisms derived from combination of optimum FGM-POFA and alkali resistant glass (ARG) to form TFGM-POFA with the minimum 2 mm of mortar thickness between the layers. The total numbers of 39 specimens of concrete prisms size of 100 mm x 100 mm x 500 mm were prepared with 2, 4, 6 and 8 layers of TFGM-POFA. This study also involves the different application of strengthening materials which are; mortar OPC and mortar OPC + ARG. Experimental works include three point bending tests on concrete prisms to determine the effect TFGM-POFA layer on concrete prisms. In addition to prism specimens, seven (7) RC beams with the size of 150 mm x 200 mm x 2500 mm were strengthened and tested with TFGM-POFA, mortar OPC and mortar OPC + ARG. The laboratory testing was conducted in four bending tests on RC beams. From the result, the optimum FGM-POFA was identified at 10 % of POFA replacement. The application of TFGM-POFA for all layers on concrete prisms is effectively enhancing the structures strength compared to the unstrengthened prism. The application of TFGM-POFA increased 36 % of the load carrying capacity of RC beams compared to unstrengthened RC beam. In conclusion, the best percentage is at 10 % of POFA replacement. The utilization of TFGM-POFA proven in increasing the flexural strength and significantly delaying the failure of concrete structure and TFGM-POFA 4 lead to a significant increase in the flexural load of RC beams